Factors related to the knowledge of implementing nurses in handling emergency patients - Badaruddin; Baso Witman Adiaksa; Fatmawati (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: The effectiveness of emergency care heavily depends on the knowledge and skills of nurses. Errors in emergency treatment often lead to severe disability or death, highlighting the need for ongoing nurse training. This study aims to identify factors related to the knowledge of implementing nurses in handling emergency patients. Method: An analytical survey with a cross-sectional approach was used, involving 30 respondents. Data were analyzed using univariate and bivariate techniques, including the Chi-Square test, with a significance level of α = 0.05. Results: The majority of respondents were aged 20–30 (80%), had higher education (53.3%), and were relatively new in service (60%). More than half (53.3%) had received emergency training. Bivariate analysis revealed significant relationships between knowledge and education (p = 0.011), length of service (p = 0.007), and training attendance (p = 0.014). Nurses with higher education, longer service, and formal training demonstrated better emergency handling knowledge. Conclusion: Education, experience, and training significantly influence nurses’ knowledge in emergency care. Continuous professional development, through formal education and certified emergency response training, is recommended to improve nursing care quality in emergencies.